Distribuição espacial de macroinvertebrados bentônicos em riachos da região central do Rio Grande do Sul, Brasil - Salvarrey, Andrea Vanessa Batalla (2010)
The knowledge of the role of physical and biological processes on animal community distribution is influenced by the spatial scale adopted in ecological studies. Due the scarcity of studies of distributional patterns of benthic macroinvertebrates in multiple scales in tropical and subtropical regions, this paper analyzes the structure of benthic macroinvertebrate communities in different spatial scales (among small watersheds and different river orders of each watershed) and the influence of certain environmental variables on these communities. The sampling was performed with Surber sampler in the small watersheds of the Vacacaí-Mirim River (August, 2008), and the Ibicuí-Mirim and Tororaipí rivers (August 2009). In each watershed were selected four sampling sites following the longitudinal gradient (stretches of 1st, 2nd, 3th and 4th orders. The environmental factors analyzed were: water temperature, pH, electrical conductivity, dissolved oxygen, substrate granulometry and presence of aquatic and riparian vegetation. A total of 10.985 individuals, 42 families and 129 taxa were collected and, in general, the dominant taxa were Simuliidae (14%), Naididae (13%), Cricotopus sp. 1 (13%), Cricotopus sp. 2 (8%) (Chironomidae), Paragripopteryx (5%) (Gripopterygidae) and Americabaetis (5%) (Baetidae) representing 58% of the total specimens collected. There were no differences in macroinvertebrate richness among watersheds, however, the community structure showed differences among the three watersheds. The stretches of 3th and 4th orders showed higher richness than the stretches of 1st and 2nd orders. Additionally, there was recorded difference among communities structure of different orders stretches (56%). In general the environmental variables that influenced the distribution of the communities were granulometry, dissolved oxygen, electrical conductivity and aquatic vegetation. The macroinvertebrates characteristic of 1st and 2nd order stretches of the Vacacaí-Mirim River and of 1st order of the Tororaipí River watersheds where influenced mainly by bigger granulometry and dissolved oxygen, while the macroinvertebrates associated to the 3th and 4th order stretches were influenced by the higher electrical conductivity. The small watersheds of the Ibicuí-Mirim (except the 2nd order stretch) and Tororaipí rivers (except the 1st and 4th order stretches) did not show difference concerning the river orders, and were associated to the smaller electrical conductivity and absence of aquatic vegetation. The 4th order stretches of the Tororaipí River was segregated of the other stretches due to its smaller granulometry. The granulometry did not influence the small watershed of the Ibicuí-Mirim and Tororaipí rivers (except the 4th order stretches) due to the presence of fine substrate, while the Vacacaí-Mirim River watershed showed coarse substrate. This difference is probably determined by the fact that the Vacacaí-Mirim River represents a tributary of a different and bigger hydrographic watershed, the Jacuí River Basin, while the others small watersheds represents tributaries of the Ibicuí River Basin. Possibly, the Jacuí River Basin have higher electrical conductvity, since this factor was high in all the sampled stretches, being encreased by the proximity to urban areas with domestic sewage and agricultural activities near the river banks. In the small watersheds of the Ibicuí-Mirim and Tororaipí rivers, the difference between the community structures is possibly related to environmental features, such as finer substrate in both rivers and well developed riparian vegetation in the Tororaipí River.